Gerba - Guglielmo Finotti (La reggenza di Tunisi considerata nei suoi rapporti geografici-storici-archeologici-idrografici-commerciali-agricoli-statistici, 1856)
Keywords: Artisanat -- Djerba; Djerba -- Histoire; Géographie -- Djerba

جربة بين ثوابت المنظومة الجزيرية وضرورات الحداثة - الفهري, عبد الحميد (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
"يبقى سؤال مدى بقاء جربة جزيرة ضمن المنظومة الجزيرية قائما بل ملحا ويحتاج إلى نظر وتبصّر. هل ما زالت جربة تستجيب لشروط الانتماء للجزر أم غادرتها؟ هذا السؤال يحتاج إلى العودة لتحديد مفاهيم وضبط شروط لا يستقيم بدونها تحديد انتماء جربة إلى عالم الجزر والمنظومة الجزيرية من عدمه. إنّنا نحتاج بموجب طرح هذه الأسئلة إلى تعميق البحث في مفهوم الجزيرية من جوانب عدة يتصدّرها الانتروبولوجي والأتنوبولوجي علاوة على أبعاد اقتصادية واجتماعية ضمن قراءة تاريخية ترصد هذا التطوّر وتحاول تحليله. لكن الجزيرية هي كذلك رصيد لا يمكن حصره من الحنين (النوستالجيا) والروابط التي تتشكل بين المعزولين لتلد نظاما تضامنيا قد يعادل الاقتصادي قوّة وربما يفوقه في ميزان الوجدان. وطبعي أنّ تعميق جانب التطوّر يطرح بالضرورة محاولة كشف تداعيات الزمنين المعاصر والحديث في ثوابت جربة الجزيرية فيما يهمّ نمط العيش وما لحق بالجزيرة من تحولات في بُناها بعد الدفع بها نحو اقتصاد سياحي ضمن اختيارات الدولة. فهل كانت الجزيرة مؤهلة لتتقبل جملة من المتغيّرات في زمن قياسي انعكست تداعياتها على تراثها المادي وغير المادي. إن الانقلاب الحاصل لمكونات جربة الاقتصادية والاجتماعية خلال الستة عقود السابقة أعمق من أن يكون مجرّد تطوّر ونموّ... إنّه فعل ضخم في صميم انتماءها الجزيري يستوجب تدقيق المآلات الحاصلة على هوية جربة ووضعها في التصنيف الذي يلائمها."
Keywords: Géographie -- Djerba

جزيرة جربة: تعدّد الأبعاد - بورقو, المنجي (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
Keywords: Géographie -- Djerba

Préface - Bourgou, Mongi (جزيرة جربة: التاريخ والإنسان والمجال = Djerba: Histoire, Homme et espace, 2025)
Keywords: Géographie -- Djerba

أهالي جربة وتأقلمهم مع قساوة المناخ المحلّي - بورقو, ملاك (جزيرة جربة: التاريخ والإنسان والمجال = Djerba: Histoire, Homme et espace, 2025)
Keywords: Géographie -- Djerba

جربة في الدراسات الجغرافيّة والتاريخية - بن عثمان, يوسف (جزيرة جربة: التاريخ والإنسان والمجال, 2025)
Keywords: Géographie -- Djerba

Cartes d'interprétation géologique et structurale de certaines régions de la Tunisie - Bergman, Knox (1963)
Keywords: Cartes -- Djerba; Géographie -- Djerba

Une pédagogie de l'environnement sur un paysage : opération pilote d'interprétation de l'environnement méditerréanéen de Djerba - Tunisie - Coopération franco-tunisienne pour l'environnement
Keywords: Géographie -- Djerba

Dissertation sur les Syrtes et les Marées de la Mer Méditerranée - Mann, Abbé (Mémoires de l'Académie Royale des Sciences, des Lettres et des Beaux-Arts de Belgique, 1788)
Keywords: Géographie -- Djerba

Contribution à la géographie culturelle du Sud Tunisien Djerba comme modèle - Suter, Karl (‎⁨أيام في الترجمة⁩, 2016)
Keywords: Géographie -- Djerba

A Letter to Sir Hans Sloane, Bart. R. S. Praes. Containing a Geographical Description and Map of the Kingdom of Tunis, with a Postscript Relating to the Cure of Intermittent Fevers in Those Parts; By the Reverend Mr. Tho. Shaw, Chaplain to the English Factory at Algier - Shaw, Thomas (Philosophical Transactions, 1775)
Keywords: Géographie -- Djerba

Collation einer Vaticanischen Handschrift des Pomponius Mela (Aus dem 11ten des 12ten Jahrh.) - Pressel, Th. (Rheinisches Museum für Philologie, 1843)
Keywords: Géographie -- Djerba

Djerba - Latrache, Leila (Généalogie des villes de Tunisie : au carrefour des deux mondes, 2021)
Keywords: Géographie -- Djerba

Djerba a Case Study in the Geography of Isolation - Karabenick, Edward (Journal of Geography, 1971)
Keywords: Géographie -- Djerba

جربة ومحيطها البحري والقاري: ‏بحوث في التاريخ والجغرافيا والحضارة‏: ‏أعمال الدورة 12 والدورة 13 لملتقى البشير التليلي - بورقو, المنجي (مركز النشر الجامعي‏, 2016)
Keywords: Géographie -- Djerba

Djerba L’île des Lotophages - Tlatli, Salah-Eddine (Cérès Editions, 1967)
Keywords: Géographie -- Djerba

L’île de Djerba - Tlatli, Salah-Eddine (Revue tunisienne, 1941)
Keywords: Géographie -- Djerba

L’île de Djerba (suite et fin) - Tlatli, Salah-Eddine (Revue tunisienne, 1942)
Keywords: Géographie -- Djerba

La Tunisie du Sud-Est, géographie d’une région marginale, marginale et dépendante - Mzabi, Hassouna (Publications de l’université de Tunis, 1993)
Keywords: Géographie -- Djerba

Lotophagitis - Heylyn, Peter (Cosmographie in four bookes : containing the chorographie and historie of the whole vvorld, and all the principall kingdomes, provinces, seas and isles thereof, 1652)
Keywords: Géographie -- Djerba

Polyhistor - Solinus, Caius Julius (C. L. F. Panckoucke, 1847)
Keywords: Géographie -- Djerba

Zizu, l’île mystérieuse d’al-Idrisi - Prevost, Virginie (Acta Orientalia Belgica, 2005)
Keywords: Géographie -- Djerba

Etude de l’évolution de l’occupation et l'utilisation du sol dans l’île de Djerba à l'aide d'un SIG - Ben Ghorbal, Tarek (Université de Lyon, 2014)
Keywords: Géographie -- Djerba

Ḏj̲arba - Despois, Jean; Mantran, Robert (Encyclopédie de l'Islam, 1965)
Keywords: Géographie -- Djerba

Djerba: Avant et après - Sigisbert, Geneviève (Europe Outremer, 1974)
Keywords: Géographie -- Djerba

Djerba. Aperçus sur les paysages et la vie d’une île méditerranéenne - Marbeau, Victor; Garenne, R. (Acta Geographica, 1962)
Keywords: Géographie -- Djerba

Räumliche Entwicklungsprozesse in Tunesien: e. Projektbericht - Rauch, Theo (Inst. für Anthropogeographie, Angewandte Geographie u. Kartographie d. Freien Univ., 1979)
Keywords: Géographie -- Djerba

Jerba : les mutations récentes d'un système insulaire - Neifar, Bassem (M@ppemonde, 2005)
Keywords: Géographie -- Djerba

Djerba et le canal d’Adjim et paysage de Djerba - Despois, Jean (Acta Geographica, 1962)
Keywords: Géographie -- Djerba

L’île de Djerba - Bazy, G. (Encyclopédie mensuelle d’Outre-Mer, 1955)
Keywords: Géographie -- Djerba

Djerba: Beitrag zur Kulturgeographie Südtunesiens (Djerba: A Contribution to the Human Geography of Southern Tunesia) - Suter, Karl (Erdkunde, 1960)
The isle of Djerba in southern Tunisia, only 514 sq. Km. large, belongs to the steppe zone of the southern Mediterranean, and its climate is characterised by hot and dry summers and mild, moderately humid, winters. This climate permits the successful cultivation of olives and dates, and in addition modest grain and vegetable growing is practised. The inhabitants distinguish four types of cultivated plots: menzel (garden with dwelling house), djnän (fruit garden), sania (vegetable garden with well for irrigation) and frawa (olive grove). Except for the latter type it is typical of all these gardens to be surrounded by high hedges. Djerba's characteristic settlement type is dispersed. The siting of the farmsteads is utterly independent of edaphic features as occurrence of water, altitude, topography and soil types. This independence is possible since the Djerbis depend for their water supply on wells. There is at least one per dwelling house, but in many cases there are two. Borings for suitable freshwater, apart from a single case, have so far had no success. The dwelling house of the island (called dar) consists of a single room which is divided into three sections. The central section serves as living quarters, whereas the adjoining ones on either side are used for sleeping. One of the latter is regularly covered by a dome (quba); this is used during the winter. The other is covered by a cubical structure with windows (ghorfa). This is used for sleeping in summer. In the latter case the sleeping accommodation is raised 3 m. above the ground and the washing facilities are underneath this raised bunk. Two or three houses are normally combined in a single structure (haouch); this is inhabited by related families and has also communally used rooms as kitchen and storage space. Somewhat different from this are the Jewish houses of the two settlements Hara Kbira and Hara Shrira. The total number of inhabitants of the isle is 60,000; they are Berbers, or rather Arabised Berbers. They belong to two different Mohammedan denominations, the Malikis and the Ibadites. There are numerous mosques on the isle. The main occupation is horticulture, additional ones are fishing, pottery and the making of carpets and wall mats. Since these occupations are insufficient to provide an adequate livelihood for the population, many Djerkis emigrate, especially to the towns of Tunisia. There they have a high reputation as traders in cloth and spices. Emigration is, however, only of the temporary type. The principal settlement is the small market town of Houmt-Souk.
Keywords: Géographie -- Djerba

Enjeux de la Tunisie orientale : un territoire développé et un environnement à protéger - Chouari, Walid; Belarem, Mongi (Confins, 2017)
Keywords: Géographie -- Djerba

L'île de Djerba - Delmas, Yves (Cahiers d'Outre-Mer, 1952)
Keywords: Géographie -- Djerba